Respuesta agronómica de las variedades de café geisha, sarchimor y manabì con fertilización orgánica e inorgánica en el centro esperimental Sacha Wiwa. - Muñoz Moreira, Vanessa Sofía (2022)
The research was carried out in the experimental center "Sacha wiwa" Guasaganda parish with the purpose of evaluating the agronomic response of the coffee varieties Geisha, Sarchimor and Manabi with organic and inorganic fertilization. The objectives were: To establish the best dose of organic and inorganic fertilization, to determine the effects of organic and inorganic fertilizer on the development of coffee plants and to evaluate the costs for each experimental treatment. The research lasted 120 days and was carried out at the "Sacha wiwa" experimental center located in the Guasaganda parish. A Complete Block Design (CBD) was used with nine treatments and five replications, Geisha coffee + medium fertilization and high fertilization and the control treatment; Sarchimor coffee + medium fertilization and high fertilization and the control treatment; Manabi coffee + medium fertilization and high fertilization and the control treatment. 300 experimental plants were used. The results show that in the soil analysis the pH was medium acid, organic matter, calcium and zinc were in medium values, potassium, phosphorus, magnesium, sulfur, manganese and boron in low concentrations. In the variable plant height, without fertilizer, Sarchimor stood out. In the fertilizer treatments, the variety Manabí + Medium phosphorus. In stem diameter without fertilization, the Sarchimor variety. With fertilization, Manabí + Medium phosphorous; with reference to costs, the dose with high concentration of phosphorous contains the highest costs for each variety of coffee used while the lowest cost corresponds to the varieties to which no fertilizer was applied.